Fertility, pregnancy, and prolactinoma: A survey of pituitary surgeons' view and review of the literature. (August 2017) - Jean, Walter C.; Felbaum, Daniel R.
Highlights: Prolactinomas make women infertile, and many female prolactinoma patients seek treatment to restore fertility. Medical guidelines recommend the use of dopamine agonist for this, but these guidelines are imperfect. Some surgeons may consider surgical treatment a legitimate option for some patients. The topic of "fertility, pregnancy and prolactinoma" requires more attention, education and debate. Abstract: Objective: Pituitary surgeons frequently encounter female prolactinoma patients seeking treatment to restore fertility. Current medical guidelines recommend using dopamine agonist (DA) for this, but for fetal safety, DA should stop upon pregnancy confirmation. The probability that prolactinoma may grow during pregnancy makes this last recommendation imperfect. With the advances in endoscopic surgery, we queried the potential role for surgery in these infertile patients, who may be ambivalent about both stopping and continuing DA while pregnant. Methods: An anonymous survey was sent to pituitary surgeons to investigate how they would advise prolactinoma patients on treatment of infertility, and counsel them about pregnancy. Directories from various US-based neurosurgical societies were culled. Surgeons who designated themselves as "skull base"/"pituitary" were surveyed. Results: Seventy-six surgeons responded (41%). The majority (67%) adhered to medical guidelines for microprolactinoma, but 26% recommended surgery. However, for a macroprolactinoma at diagnosis, the number of surgeons who recommended DA treatment vs. surgical treatment were almost evenly split ( χ 2 p  = 0.06). The practice setting of a multidisciplinary clinic with endocrinologists did not significantly influence our respondents' choice. For a patient who presented after becoming pregnant on DA, our respondents were against surgery to prevent tumor growth (96%). Conclusion: A review of the current literature shows that both medical and surgical therapy have flaws. Significant numbers of surgeons considered surgery a legitimate option for prolactinoma patients seeking to be pregnant. The divergence between these surgeons' opinion and current medical guidelines warrants further investigation and discussion.